2022
DOI: 10.1186/s12885-022-09247-3
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous oestradiol and progesterone as predictors of oncogenic human papillomavirus (HPV) persistence

Abstract: Background High-risk human papillomavirus (HR-HPV) is the main aetiological factor for the development of cervical cancer. While nearly 70% of HR-HPV infections are cleared within 12 months, in the remainder of women they persist and can progress into cervical cancer. Oestradiol and progesterone have been shown to be involved in the development and progression of cervical cancer. The objective of this study was to investigate, for the first time, whether diurnal oestradiol and progesterone are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While the estrogen dose administered in our study has been shown to induce conditions consistent with persistent estrus in mice ( 54 ) models that rely upon endogenous physiological estrogen levels warrant investigation in our studies. Epidemiological studies have identified associations between several conditions that elevate estradiol levels in humans with increased risk for HPV persistence and subsequent neoplastic progression in the female reproductive tract, such as long-term oral contraceptive use, pregnancy, and multiparity ( 75 , 116 122 ). Given that estradiol levels also increase during the murine gestational period ( 123 ), future studies could explore the effect of pregnancy and/or multiparity on MmuPV1 viral persistence, clearance, and malignant progression under conditions where estrogen levels are naturally increased as opposed to exogenous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the estrogen dose administered in our study has been shown to induce conditions consistent with persistent estrus in mice ( 54 ) models that rely upon endogenous physiological estrogen levels warrant investigation in our studies. Epidemiological studies have identified associations between several conditions that elevate estradiol levels in humans with increased risk for HPV persistence and subsequent neoplastic progression in the female reproductive tract, such as long-term oral contraceptive use, pregnancy, and multiparity ( 75 , 116 122 ). Given that estradiol levels also increase during the murine gestational period ( 123 ), future studies could explore the effect of pregnancy and/or multiparity on MmuPV1 viral persistence, clearance, and malignant progression under conditions where estrogen levels are naturally increased as opposed to exogenous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in HPV-16 positive cell lines CaSki and SiHa demonstrated that estrogen increased proliferation of SiHa cells and appeared to protect CaSki cells from apoptosis ( Ruutu et al, 2006 ). In human studies, it has been demonstrated that HR-HPV positive women had significantly higher morning and daily estradiol levels compared to HR-HPV negative women ( Fischer et al, 2022 ). Estrogen receptors (ER) have been identified in epidermal keratinocytes and dermal fibroblasts of the vulva, which opens up the possibility that there may be an estrogen effect inducing oncogenic HPV activity on the vulva ( MacLean et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%